Participation in Developing Agro-tourism Attractions of Local Government Organizations in Pathum Thani and Nakorn Nayok Provinces - Jungprawate, Patcharin (Journal of Cultural Approach, 2018)
This study was conducted to examine participation in developing agro-tourism attractions of local government organizations in Pathum Thani and Nakorn Nayok provinces for develop to sustainable agro-tourism and to compare the participation of representatives from local government organizations in both provinces in developing agro-tourism attractions by gender, age, education, and work experience. The results showed that The representatives from local government organizations participated in developing agro-tourism attractions of local government organizations in Pathum Thani and Nakorn Nayok provinces as a whole at a medium level. When each aspect was considered, planning of development and maintenance was at a high level, followed by safety, advertisement and public relations, management, and survey and data collection at medium levels. With regards to the hypothesis, the representatives from local government organizations in Pathum Thani and Nakorn Nayok provinces with different genders, ages, and experience had no different participation rates in developing agro-tourism attractions. The representatives with different level of education had different participation in developing agro-tourism attractions at the 0.05level of significance.